Spatial distribution of vegetation diversity, timber production, and carbon storage in secondary tropical rainforest at South Kalimantan, Indonesia - SUYANTO SUYANTO; YUSANTO NUGROHO; MOEHAR MARAGHIY HARAHAP; LIA KUSUMANINGRUM; PANDU YUDHA ADI PUTRA WIRABUANA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Suyanto, Nugroho Y, Harahap MM, Kusumaningrum L, Wirabuana PYAP. 2022. Spatial distribution of vegetation diversity, timber production, and carbon storage in secondary tropical rainforest at South Kalimantan, Indonesia. Biodiversitas 23: 6147-6154. Sustainable management in secondary tropical rainforests requires basic information about stand characteristics, mainly related to productivity and biodiversity. This study aimed to quantify vegetation diversity, timber production, and carbon storage from various sites of secondary forests in South Kalimantan. Forest inventory was conducted using a census method at seven different natural forest management unit compartments. Four parameters were measured from each tree, including the type of species, commercial categories, tree diameter, and tree height. Individual tree volume and biomass were estimated using allometric equations, while carbon storage was determined using a conversion factor from biomass. Three indicators were used to evaluate vegetation diversity: richness, heterogeneity, and evenness. The analysis of correlations was applied to examine the relationship between vegetation diversity and stand productivity with a significant level of 5%. Results found that there were 41 tree species in the study site comprising 20 commercial and 21 non-commercial species. The highest richness (R') was recorded in compartment 18X by approximately 4.0, while the most increased heterogeneity (H') and evenness (E') were observed in compartment 18Y by around 2.4 and 0.7, respectively. The accumulation of timber production varied in each site, with a range of 45.46-68.32 m3 ha-1. The highest carbon storage was noted in compartment 19Y (38.74±1.79 t C ha-1), while the lowest was found in compartment 18W (20.76±0.93 t C ha-1). The relative contribution of commercial species to timber production and carbon storage was substantially higher than non-commercial species at all sites. However, there was not a significant correlation between vegetation diversity and stand productivity (P>0.05). Overall, our study concluded that the secondary tropical forest ecosystems in the site had good vegetation diversity, timber production, and carbon storage.